Silver Nanoparticles: Synthesis in Newly Formed Ternary Deep Eutectic Solvent Media, Characterization and their Antifungal Activity - K, Sarjuna; D, Ilangeswaran (Current Nanomaterials, 2023)
Background: When halide salts and hydrogen bond donors are combined, they produce deep eutectic solvents, which have a lower freezing/melting point than the individual components. At room temperature, they have emerged as viable alternatives to ionic liquids. The wonderful features of deep eutectic solvents, such as humidity tolerance, high-temperature stability, low cost, nonhazardous, reusable, and recyclable nature, allow them to replace ionic liquids. Objective: This study aimed to prepare two newer ternary deep eutectic solvents using malonic acid with glucose and glutamine and malonic acid with fructose and glutamine. Moreover, using the prepared ternary deep eutectic solvents, silver nanoparticles were synthesized, and their antifungal behavior was studied. Methods: The ternary deep eutectic solvents were prepared by the evaporation method in water and subjected to measure the properties, such as density, pH, conductivity, viscosity, and absorption frequencies of Fourier Transform Infrared Spectroscopy. The prepared deep eutectic solvents were then used for the synthesis of silver nanoparticles by the chemical reduction method in the presence of hydrazine hydrate as a reducing agent and sodium hydroxide as a stabilizing agent. The synthesized nanoparticles were characterized by UV-Visible Spectroscopy, Fourier Transform Infrared Spectroscopy, X-ray diffraction, scanning electron microscopy, and energy dispersive X-ray analysis techniques. Results: The characteristic absorption peak of UV-Visible spectroscopy showed that silver nanoparticles were formed. FTIR exposed the metallic and other bonding of the nanoparticles and the capping materials. From the XRD pattern, we found the crystalline nature of silver nanoparticles and the images formed in the SEM were in the nanoscale. The average particle size of silver nanoparticles ranged from 116.87 nm to 26.61 nm. Conclusion: In our study, two types of novel ternary deep eutectic solvents were developed. They act as a better solvent media for the synthesis of silver nanoparticles, and the synthesized nanoparticles show antifungal behaviors against some microbes.
Keywords: SEM